Collider signals of baryogenesis and dark matter from B mesons: a roadmap to discovery - Alonso Álvarez, Gonzalo; Elor, Gilly; Medina, Miguel Ángel (Physical review, 2021)
Low-scale baryogenesis could be discovered at B factories and the LHC. In the B-Mesogenesis paradigm [G. Elor, M. Escudero, and A. E. Nelson, Phys. Rev. D 99, 035031 (2019)], the CP-violating oscillations and subsequent decays of B mesons in the early Universe simultaneously explain the origin of the baryonic and the dark matter of the Universe. This mechanism for baryo- and dark matter genesis from B mesons gives rise to distinctive signals at collider experiments, which we scrutinize in this paper. We study CP-violating observables in the B0q−¯B0q system, discuss current and expected sensitivities for the exotic decays of B mesons into a visible baryon and missing energy, and explore the implications of direct searches for a TeV-scale colored scalar at the LHC and in meson-mixing observables. Remarkably, we conclude that a combination of measurements at BABAR, Belle, Belle II, LHCb, ATLAS, and CMS can fully test B-Mesogenesis.
Gesehen am 05.11.2021